Letramento para a docência em matemática nos anos iniciais - Tozetto, Annaly Schewtschik (2010)
Nowadays, reflect on the initial training of teachers who teach mathematics in the early years of elementary school is of paramount importance since, due to legal requirements, the training started to take on a higher level. Currently, this is the responsibility of Pedagogy courses, which, after reformulations in their curricula, are based on the principle that training in the paradigm of teaching skills and abilities. This research aims at investigating skills and teaching skills that give a position to exercise their teaching professor in mathematics at the stage of basic education, committed to the mathematics education of their students. This led us to wonder whether the powers and abilities to teach mathematics are being developed in t he process of initial formation of the current curriculum for the Bachelor of Education, State University of Ponta Grossa (UEPG), after the curriculum reform, and if result in a literacy for teaching mathematics in the early years of elementary school. Our aim was to reveal to what extent the current Educational Project of Bachelor of Education includes the development of such skills and teaching skills for working with the math, showing the points where there are gaps in what we are calling for literacy teaching math in the early years. A qualitative, this research relied on procedures of content analysis (Bardin, 2009) for the analysis of empirical evidence, grounded in the categorical theory of semiotic representation registers (Duval, 1999 ,2004). First we analyzed official documents (National Curriculum Guidelines) regarding the development of skills and abilities in the process of initial training. Such skills are founded by teachers knowledge of Shulman (1986) and Gauthier (2006). From this, we analyzed the Educational Project of the Bachelor of Education (PPCLP) of UEPG, to verify what he is contemplating those powers listed in official documents. We found the implied powers on menus of some subjects and we infer that are conditional on a crosscurricular work of the trainer. As we had to verify the effectiveness of what we find in PPCLP, we developed other instruments to collect information that came to meet this goal. The first had questions that would reveal the identity of teaching undergraduates, so that we could verify the extent to which this course is reflected as a training course for teachers, since to assume responsibilities for the mathematics education of their future students, with undergrad uates need to identify themselves as teachers. The second instrument, the more specific issues had simulated the process of teaching and learning of mathematics in order to verify the actual realization of the implication that we find in PPCLP. The results showed us a lack of knowledge of mathematical content, the mathematics curriculum of the early years of elementary school and the pedagogical processes involved in mathematics by those licensees, showing us that PPCLP is flawed both in the question of identification of their teaching licensees regarding the development of skills and abilities, thereby undermining literacy for teaching mathematics in the early years.